The Mediating Role of Locus of Control in the Relationship between Environmental Education and Pro-Environmental Behavior among University Students - Dewi Indah Pratiwi; Budiaman Budiaman; Guspri Devi Artanti (Jurnal Edusci, 2026)
Aims. This study investigates the relationship between environmental education and pro-environmental behavior among university students, with locus of control as a mediating variable. Environmental education is believed to enhance awareness and values related to sustainability, yet its effectiveness may depend on individuals’ perceived control over their actions. Methods. The study involved 200 students from various academic programs who had taken environmental courses. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for data analysis. Result. The results show that environmental education positively influences pro-environmental behavior, and locus of control significantly mediates this relationship. Conclusion. Students with an internal locus of control are more likely to translate environmental knowledge into actionable behavior. Implementation. The study suggests that educational strategies should emphasize the development of personal agency in environmental matters to support behavioral change.